Flexible Dual Band Dipole Antenna with Electromagnetic Band Gap - Abu, Maisarah; Md. Ali, Siti Adlina; Hassan, Hasnizom; Mohamad, Najmiah Radiah (Institute Of Advanced Engineering And Science (IAES), 2017)
Flexible dual band dipole antenna incorporates with Electromagnetic Band Gap (EBG) to improve the well-known low profile characteristics of dipole antenna. The antenna operates at 2.45 GHz and 5.8 GHz which is printed on Fast film with 0.13 mm thickness. While the EBG is designed at 5.8 GHz by using Arlon AD350 with 1.016 mm thickness. EBG works as a ground plane for the antenna and helps by improving the realized gainandradiation pattern. Besides, EBG also act as a filter as the resonant frequency of the antenna is close to the EBG band gap. The 2.45 GHz of is eliminated while the performances of antenna at 5.8 GHz is improved. Thus the realized gain is increased up to 6.86 dB and the back lobes are clearly reduced. The designs of dipole antenna with EBG application such as Wifi and others on-body communication devices.